CONTINUITY OF MIDWIFERY CARE IN PREGNANCY, LABOUR AND POSTPARTUM PERIOD IN PBM SITI MARLINA, AMd.Keb NGUNUT BOJONEGORO - Nur Azizah; Sri Luluk; Wiwik Muhidayati; Ni'matus Sholihah (International Journal of Midwifery Research, 2023)
Good management during the womb, during labor, after birth and monitoring subsequent growth and development will produce a healthy baby. The research was to apply Sustainable Midwifery Care to Ny. R from pregnancy to the puerperium. This Final Report is in the form of a case study using the midwifery management approach and documented in the SOAP format. The subject of this research was Ny. R GIIP0A1 32-33 weeks gestational age. The results of the study were obtained that the care of a pregnancy that was initially a pregnancy with Chronic Energy Less and the end result of the pregnancy was physiological. In childbirth care at PBM Siti Marlina, AMd, Keb., Ngunut Village, Dander District, Bojonegoro Regency, time: 05.10 WIB, the baby was born spontaneously.. The postpartum midwifery care has been carried out in accordance with the postpartum service standards that is carried out 4 times home visit. Midwifery care for postpartum contraception services is done (21 days after giving birth to a baby), with the result that the mother has not yet decided on the contraceptive to be used because she has never used contraception before and after receiving an explanation of the various contraceptive contraceptive methods Ny. R used 3-month injection contraception. It is expected that health workers will play an active role in providing quality midwifery services for mothers from pregnancy to family planning both physiologically and pathologically according to midwifery service standards so as to reduce the increase in MMR and IMR.